2011
DOI: 10.1007/s11837-011-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Collagen scaffolds for orthopedic regenerative medicine

Abstract: How would you……describe the overall signifi cance of this paper?Collagen and collagen-based scaffolds offer distinct advantages when selected as biomaterials for use across a broad spectrum of regenerative medicine applications. However, relatively poor mechanical properties are often perceived to limit their usefulness for orthopedic applications. These problems can be overcome through enhanced crosslinking mechanisms or through the addition of a second, stiffer phase such as hydroxyapatite, thus allowing tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 122 publications
1
19
1
Order By: Relevance
“…Chitosancollagen combinations in the form of scaffolds are normally used for attaching and cell migration, delivering and maintaining the cells from biochemical factors, enabling the diffusion of vital cell nutrients and both producing and exerting mechanical and certain biologic influence in order to modify the behavior of the cell phase. 15,16 In other studies revealed that osteoblasts increased significantly at the outset of the 20 days of addition of the scaffold in the experimental specimens, 17 however, in our study blood vessels were formed on Day 14,18,19 and osteogenesis started on the same day after the graft was implanted in the bone, so the observation of this study was on day 14. 15 50:50 chitosan-collagen scaffold treatment is significantly different to collagen and chitosan scaffolds because the latter are porous ± 650μm-850μm.…”
Section: Discussioncontrasting
confidence: 58%
“…Chitosancollagen combinations in the form of scaffolds are normally used for attaching and cell migration, delivering and maintaining the cells from biochemical factors, enabling the diffusion of vital cell nutrients and both producing and exerting mechanical and certain biologic influence in order to modify the behavior of the cell phase. 15,16 In other studies revealed that osteoblasts increased significantly at the outset of the 20 days of addition of the scaffold in the experimental specimens, 17 however, in our study blood vessels were formed on Day 14,18,19 and osteogenesis started on the same day after the graft was implanted in the bone, so the observation of this study was on day 14. 15 50:50 chitosan-collagen scaffold treatment is significantly different to collagen and chitosan scaffolds because the latter are porous ± 650μm-850μm.…”
Section: Discussioncontrasting
confidence: 58%
“…Tough bundles of collagen fibers are a major component of the extracellular matrix (ECM) that provides support for cells in most tissues [3,4]. The triple helical structure of collagen enables adhesiveness of cells and is important for the proper assembly of the ECM [5]. The levels of hydroxylation, glycosylation, cross-linking and the mechanical properties of collagen are dependent on a number of important tissue properties, including tissue type, age, and hormonal status [2].…”
Section: Introductionmentioning
confidence: 99%
“…19 Collagen type I is the most universal type-found in bone, skin, tendons, ligaments, and other tissues-and its ubiquity has made it one of the most frequently used raw materials in tissue engineering over the past decade. 20 Hyaline cartilage and nucleus pulposus are the main tissues that contain little collagen type I in their native ECM, but are rich in collagen type II. 10,21,22 The main advantages of utilizing collagen as a part of a tissue engineering scaffold include its intrinsic cell adhesion motif RGD, biocompatibility, and bioresorbability.…”
Section: Collagenmentioning
confidence: 99%
“…23 Poor mechanical properties and rapid degradation are the main drawbacks when considering collagen as a scaffold component. 17,20,23 The following sections will discuss the use of collagens type I and II in tissue engineering scaffolds and applications of collagen as a …”
Section: Collagenmentioning
confidence: 99%
See 1 more Smart Citation